Estimation of Improvements in Mortality in Spectrum Among Adults With HIV Receiving Antiretroviral Therapy in High-Income Countries - Trickey, Adam; Glaubius, Robert; Pantazis, Nikos; Zangerle, Robert; Wittkop, Linda; Vehreschild, Janne; Grabar, Sophie; Cavassini, Matthias; Teira, Ramon; d'Arminio Monforte, Antonella; Casabona, Jordi; van Sighem, Ard; et al. (Journal of acquired immune deficiency syndromes (1999), 2024)
Mortality rates for people living with HIV (PLHIV) on antiretroviral therapy (ART) in high-income countries continue to decline. We compared mortality rates among PLHIV on ART in Europe for 2016-2020 with Spectrum's estimates. The AIDS Impact Module in Spectrum is a compartmental HIV epidemic model coupled with a demographic population projection model. We used national Spectrum projections developed for the 2022 HIV estimates round to calculate mortality rates among PLHIV on ART, adjusting to the age/country distribution of PLHIV starting ART from 1996 to 2020 in the Antiretroviral Therapy Cohort Collaboration (ART-CC)'s European cohorts. In the ART-CC, 11,504 of 162,835 PLHIV died. Between 1996-1999 and 2016-2020, AIDS-related mortality in the ART-CC decreased from 8.8 (95% CI: 7.6 to 10.1) to 1.0 (0.9-1.2) and from 5.9 (4.4-8.1) to 1.1 (0.9-1.4) deaths per 1000 person-years among men and women, respectively. Non-AIDS-related mortality decreased from 9.1 (7.9-10.5) to 6.1 (5.8-6.5) and from 7.0 (5.2-9.3) to 4.8 (4.3-5.2) deaths per 1000 person-years among men and women, respectively. Adjusted all-cause mortality rates in Spectrum among men were near ART-CC estimates for 2016-2020 (Spectrum: 7.02-7.47 deaths per 1000 person-years) but approximately 20% lower in women (Spectrum: 4.66-4.70). Adjusted excess mortality rates in Spectrum were 2.5-fold higher in women and 3.1-3.4-fold higher in men in comparison to the ART-CC's AIDS-specific mortality rates. Spectrum's all-cause mortality estimates among PLHIV are consistent with age/country-controlled mortality observed in ART-CC, with some underestimation of mortality among women. Comparing results suggest that 60%-70% of excess deaths among PLHIV on ART in Spectrum are from non-AIDS causes.